'A Winter's Tale': parasite control in cattle at housing. (2nd November 2019) - Forbes, Andrew
Abstract : Although some cattle farms operate year-round with stock outside, cattle are housed at the onset of winter on the majority of farms. Housing typically coincides with the onset of cold, wet weather, a decline in the quantity and quality of grazing and wet underfoot conditions leading to poaching of fields. While the transition from a fresh grass-based diet under extensive conditions outside to a controlled forage-based ration in close confinement inside requires some adaptations by both cattle and farmers, it also provides an opportunity for an assessment of parasite status and the implementation of appropriate control measures. Exposure to new helminth infections while grazing is essentially eliminated during housing; thus effective treatments can provide long-term control until turnout the following year. Obligate ectoparasites such as lice and mange mites, with short survival times off the host, can also be eliminated over winter through effective ectoparasiticide treatment of at-risk groups. To comply with the ethos of 'responsible use' of parasiticides, group treatments of cattle at housing must be justified through risk assessments, though potential negative impacts on selection for anthelmintic resistance and environmental impact can also be mitigated through manure and slurry management and disposal.